The Importance of Membership in Local Tourist Organisations for Building Bilateral Cooperation - Czernek-Marszałek, Katarzyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
One of the ways to compete for tourists is to create local tourist organisations in tourist areas. Their goal, apart from promoting tourism, is to create opportunities to establish bilateral economic cooperation between the entities associated in them. No research has been done to indicate whether affiliation in such organisations actually serves to build cooperation, how it builds cooperation or, alternatively, why it does not. This article seeks answers to these questions, and does so with the help of a case study on the Wisla Tourism Organisation (WOT) and semi-structured interviews conducted in 2013–2014 with 48 WOT members. The results of the research show that the WOT, to only a limited degree, enables the establishment of bilateral cooperation between members associated in this organisation. The reasons for this include the fact that the organisation’s members have diversified needs and interests, largely fail to actively participate in WOT meetings, suffer from a lack of clearly perceptible, measurable benefits of participating in the organisation. At the same time, the organisation charges a membership fee. The article concludes with recommendations that could be used to change the situation.